2017
DOI: 10.3390/ijms18071576
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mitochondria with the Endoplasmic Reticulum and Plasma Membrane in Calcium Homeostasis, Lipid Trafficking and Mitochondrial Structure

Abstract: Studying organelles in isolation has been proven to be indispensable for deciphering the underlying mechanisms of molecular cell biology. However, observing organelles in intact cells with the use of microscopic techniques reveals a new set of different junctions and contact sites between them that contribute to the control and regulation of various cellular processes, such as calcium and lipid exchange or structural reorganization of the mitochondrial network. In recent years, many studies focused their atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 162 publications
(217 reference statements)
3
142
0
3
Order By: Relevance
“…First, ER-mitochondria connections regulate calcium homeostasis, which is well known to be altered in AD (167,176,177). Among its many functions, mitochondrial calcium buffering capacity regulates the intracellular concentration of calcium, not only by buffering local changes in the cytosol, but also via highly regulated contacts with the plasma membrane and/or the ER (178,179). Therefore, alterations in the communication between mitochondria and these organelles can significantly impact the entry of calcium into mitochondria, affecting overall calcium signaling in the cell (180,181).…”
Section: Possible Mechanism Of Oxphos Deficiency In Neurodegenerativementioning
confidence: 99%
“…First, ER-mitochondria connections regulate calcium homeostasis, which is well known to be altered in AD (167,176,177). Among its many functions, mitochondrial calcium buffering capacity regulates the intracellular concentration of calcium, not only by buffering local changes in the cytosol, but also via highly regulated contacts with the plasma membrane and/or the ER (178,179). Therefore, alterations in the communication between mitochondria and these organelles can significantly impact the entry of calcium into mitochondria, affecting overall calcium signaling in the cell (180,181).…”
Section: Possible Mechanism Of Oxphos Deficiency In Neurodegenerativementioning
confidence: 99%
“…From the above described results it may be deducted that the absence of amino sequences 1-11 in Hst2 and 23-38 in Hst5 (compared to Hst1) dramatically compromised their uptake rates. Consequently, we assessed the uptake dynamics and subcellular targets of truncated variants, F-Hst1 1-11 , F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] to explore their role in the cellular uptake of Hst1, Hst2 and Hst5. CLSM images revealed that the uptake of the truncated variants F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] was much lower than that of the whole molecule F-Hst1 ( Figure 7A-D).…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
“…Cellular uptake of the F-Hst1 and truncated variants, such as F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 23-38 by HO1N1 epithelial cells. (A-D) CLSM images showed that a significantly higher amount of F-Hst1 accumulated in the vicinity of nuclei than F-Hst1 12-22 , while F-Hst1 1-11 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] showed only mild accumulation. (E,F) Flow cytometric analysis confirmed that F-Hst1 showed the highest cell-associated fluorescence density, which was followed by F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
“…The dynaminrelated GTPases; MFN1 and MFN2 are responsible for fusion of outer mitochondrial membranes (OMMs) and form homo-oligomeric and hetero-oligomeric complexes [5,6]. MFN2 is also present in the endoplasmic reticulum, controlling its morphology and facilitating mitochondrial calcium influx from the endoplasmic reticulum [7]). Inner mitochondrial membrane (IMM) fusion is mediated by OPA1, also a dynamin-related GTPase protein that is associated with different functions such as maintenance of the respiratory chain, IMM potential, mtDNA and control of apoptosis [8].…”
mentioning
confidence: 99%